PCR-Based Allelic Discrimination for Glucose-6-Phosphate Dehydrogenase (G6PD) Deficiency in Ugandan Umbilical Cord Blood. (1st February 2014) - Hsu, Jennifer; Fink, Deanna; Langer, Erica; Carter, Michelle L.; Bengo, Derrik; Ndidde, Susan; Slusher, Tina; Ross, Julie A.; Lund, Troy C.
<x xml:space="preserve">Abstract</x> Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common X-linked disorder in the world. G6PD deficiency puts children at risk for hyperbilirubinemia and kernicterus during the newborn period and an increased risk of severe hemolysis after exposure to many antimalarial medications. A laboratory diagnosis of G6PD deficiency is rare in the developing world due to limited resources. We developed a TaqMan-based allele-specific assay to rapidly determine rates of G6PD deficiency contributing alleles (G202A and A376G) in East Africa. We tested umbilical cord blood from 100 Ugandan newborns and found that the overall allele frequency of G202A was .13 and A376G was .32. The overall incidence of G6PD A− (G202A/A376G) was 6%; all A− variants were males. There was no correlation between G6PD deficiency and umbilical cord blood hemoglobin, white blood count, platelet count, or other hematologic parameters. Allele-specific PCR can serve as a rapid method to determine specific G6PD deficiency allele frequencies in a given population and as a diagnostic tool in a hospital setting in which laboratory resources are present.